2015
DOI: 10.1186/s13063-015-0589-1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing suicidal thoughts in the Australian general population through web-based self-help: study protocol for a randomized controlled trial

Abstract: BackgroundSuicidal thoughts are common in the general population, causing significant disability. However, a substantial number of people struggling with suicidality do not access appropriate services. Online self-help may help overcome barriers to help-seeking. This study aims to examine the effectiveness of an online self-help program targeted at reducing suicidal thoughts compared with an attention-matched control condition in the Australian adult population. This trial is based on a Dutch self-help program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…An additional 10 ongoing studies were identified at the time of the systematic search [ 52 59 ]. Further details of these ongoing trials are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 10 ongoing studies were identified at the time of the systematic search [ 52 59 ]. Further details of these ongoing trials are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… Not stated. Van Spijker, 2015 [ 59 ] RCT Australia 570 Community-dwelling adults reporting current suicidal ideation according to item five of the Columbia-Suicide Severity Rating Scale, but who do not self-report attempting suicide within the past month. iCBT: Consisting of six modules delivered once a week over a six week period.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for exclusion are reported in Figure 1 . Briefly, several articles did not meet various inclusion criteria, examples of which follow: they were not interventions designed in the West and adapted for a CALD population, but instead were designed specifically for the population [ 31 - 33 ]; the participants were not considered a CALD population [ 34 - 36 ]; the interventions were not self-help according to our standard definition above [ 37 - 39 ]; and/or no common mental disorder outcome measure was reported [ 40 - 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It compared an internet‐based cognitive–behavioral treatment program for suicidal thinking, Living with Deadly Thoughts (LwDT), and an attention‐matched control condition, Living Well. Full details of the study methodology are provided in the trial protocol (van Spijker et al., ) and primary outcomes paper (van Spijker et al., ), with a summary provided below.…”
Section: Methodsmentioning
confidence: 99%